Accuracy the Altman Method in Predicting Bankruptcy Of Property Companies - muhammad taufiq abadi; Muhammad Sultan Mubarok (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to calculate and analyse the level of financial difficulties experienced by the company using the Altman Z-Score method. The variable used in this study is the Altman Z-Score method which is proxied by the ratio of liquidity, leverage, profitability, effectiveness and market ratio. The samples used were 6 property companies listed on the Indonesia Stock Exchange from the 2019-2021 period. In this study, hypothesis testing used the Altman Z-score analysis method, with the help of the Microsoft Excel program and Statistical Package the Social Science (SPSS) VERSION 23.0. The results of testing the hypothesis of this study indicate that the altman z-Score model is very accurate in predicting company bankruptcy, further results show that the liquidity ratio, leverage, profitability, market ratio and activity determine the final value of altman z-score prediction. The third result shows that there are six companies that are in the grey area position during 2019-2021 and the rest are in a position of experiencing financial distress.